The Gamifying Learning: The Power of Edu-Monopoly to Spark Students’ Interest - a Meta-Analysis - AS Almunawwarah; Firmansyah (Jurnal Ilmiah Sekolah Dasar, 2025)
Learning interest is a crucial factor in the instructional process, as it directly influences students’ engagement and learning outcomes. However, classroom learning is still often dominated by conventional methods that are less effective in fostering students’ learning interest. One alternative instructional medium that has been widely developed to address this issue is the edu-monopoly educational game. This study aims to systematically analyze and synthesize the effectiveness of edu-monopoly as an educational game medium in enhancing students’ learning interest through a meta-analysis approach. The study employed a meta-analytic design following the PRISMA 2020 guidelines. Research articles were identified through the Google Scholar database covering publications from 2017 to 2025 using the Publish or Perish application with the keywords “instructional media,” “monopoly,” and “learning interest.” Of the 707 articles initially identified, five studies met the inclusion criteria by providing complete statistical data, including means, standard deviations, sample sizes for experimental and control groups, and effect size measures. Data analysis was conducted using JASP software version 0.95.2.0. The results of the meta-analysis indicate that the use of Edu-monopoly has a positive effect on improving students’ learning interest, with variations in effect sizes across studies but no strong evidence of publication bias. These findings imply that Edu-monopoly is a relevant and effective educational game medium for supporting more engaging learning environments and enhancing students’ learning interest.